Hypothalamic Neurogenesis as an Adaptive Metabolic Mechanism - Recabal, Antonia; Caprile, Teresa; García-Robles, María de los Angeles (Frontiers in Neuroscience, 2017)
In the adult brain, well-characterized neurogenic niches are located in the subventricular zone (SVZ) of the lateral ventricles and in the subgranular zone (SGZ) of the hippocampus. In both regions, neural precursor cells (NPCs) share markers of embryonic radial glia and astroglial cells, and in vitro clonal expansion of these cells leads to neurosphere formation. It has also been more recently demonstrated that neurogenesis occurs in the adult hypothalamus, a brain structure that integrates peripheral signals to control energy balance and dietary intake. The NPCs of this region, termed tanycytes, are ependymal-glial cells, which comprise the walls of the infundibular recess of the third ventricle and contact the median eminence. Thus, tanycytes are in a privileged position to detect hormonal, nutritional and mitogenic signals. Recent studies reveal that in response to nutritional signals, tanycytes are capable of differentiating into orexigenic or anorexigenic neurons, suggesting that these cells are crucial for control of feeding behavior. In this review, we discuss evidence, which suggests that hypothalamic neurogenesis may act as a novel adaptive mechanism in order to respond to changes in diet.